2016 IEEE 23rd International Conference on Software Analysis, Evolution, and Reengineering (SANER) 2016
DOI: 10.1109/saner.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

A Code Refactoring Dataset and Its Assessment Regarding Software Maintainability

Abstract: It is very common in various fields that there is a gap between theoretical results and their practical applications. This is true for code refactoring as well, which has a solid theoretical background while being used in development practice at the same time. However, more and more studies suggest that developers perform code refactoring entirely differently than the theory would suggest.Our paper encourages the further investigation of code refactorings in practice by providing an excessive open dataset of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting that we focus our attention on a relative small number of software systems because, as detailed in Section II-A, we relied on a publicly available dataset composed of 12,922 operations (manually validated) related to 28 different refactoring types identified in each of the considered releases [18]. Note that while other datasets are available [21], to the best of our knowledge the one built by Bavota et al is the largest one in terms of refactoring operations (12,922 vs 7,872 reported by Kadar et al).…”
Section: Empirical Study Definition and Designmentioning
confidence: 99%
“…It is worth noting that we focus our attention on a relative small number of software systems because, as detailed in Section II-A, we relied on a publicly available dataset composed of 12,922 operations (manually validated) related to 28 different refactoring types identified in each of the considered releases [18]. Note that while other datasets are available [21], to the best of our knowledge the one built by Bavota et al is the largest one in terms of refactoring operations (12,922 vs 7,872 reported by Kadar et al).…”
Section: Empirical Study Definition and Designmentioning
confidence: 99%
“…The dataset utilized in this was adopted from a previous study of 34,35 that provided extensive information regarding refactoring and source code metrics for 7 open-source Java systems (Table 1). It is composed of 37 releases of these systems and is characterized by a comprehensive manual validation process that guarantees the accuracy and reliability of the data.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…The dataset used in this research encompasses a range of refactoring types, with 23 classes and 19 methods. The data repository is available from 34,35 at http:// www. inf.u-szeged.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…Kadar et al [54] put forward the idea to examine code refactoring as a means of creating an open dataset that would be necessary for utilizing software code metrics and refactoring techniques across various versions of seven systems. Through the use of refactoring methods, the authors aimed to analyze the quality features of duplicate source code classes, as well as the effectiveness of updating source code metrics.…”
Section: Related Research To the Quality Of Codementioning
confidence: 99%